THE EFFECTIVENESS OF AUGMENTED REALITY-BASED PHYSICS LEARNING USING ASSEMBLR EDU ON STUDENTS' CRITICAL THINKING SKILLS - Marsila, Sinta; Hamdani, Dedy; Koto, Irwan (EduFisika: Jurnal Pendidikan Fisika, 2026)
In order to achieve conceptual understanding rather than rote memorization, students must analyze information, connect multiple representations, and evaluate solutions logically. This is why critical thinking is a fundamental requirement in 21st-century physics education, especially for abstract topics like fluids. The purpose of this study was to determine how well students' critical thinking abilities on fluid issues may be improved by Augmented Reality (AR)-based physics instruction utilizing the Assemblr Edu platform. At a public senior high school in Bengkulu City (N = 78), two Grade XI classes took part in a quasi-experimental study using a nonequivalent control group design. There was an experimental group and a control group. An essay-style critical thinking test that was created using Ennis's indicators served as the research tool. Gain scores, normality and homogeneity tests, independent samples t-tests, Cohen's d effect size, and N-gain were used to examine the data. The experimental group received a higher posttest mean score (M = 70.76) than the control group (M = 50.51), indicating a statistically significant difference (p < 0.001) in critical thinking abilities between the two groups. The effect size (d = 1.31) shows that AR-based instruction with Assemblr Edu significantly enhances students' critical thinking abilities. These results imply that incorporating augmented reality (AR) into physics education strengthens attempts to improve students' critical thinking abilities in static fluid issues by enabling more tangible and interactive representations of abstract fluid notions.